2003
DOI: 10.1080/02841860310017658
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality of Life of Breast Cancer Patients

Abstract: Research has indicated that several demographic and clinical factors may affect the quality of life of breast cancer patients. Few studies, however, have sufficient sample sizes for multivariate analyses to be tested. Furthermore, several important factors, such as arm morbidity, communication and comorbid illness, have not been included in quality of life models The aim of this study was to predict the simultaneous effect of these factors on long-term quality of life. Breast cancer patients (n = 990) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 22 publications
10
99
2
13
Order By: Relevance
“…This study used the subscales of body image, arm symptoms, and breast symptoms, as studies have reported longlasting problems in these areas [4,20,21]. Higher mean scores on the body image scale represent better functioning, whereas higher mean scores on the symptom scales represent more symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study used the subscales of body image, arm symptoms, and breast symptoms, as studies have reported longlasting problems in these areas [4,20,21]. Higher mean scores on the body image scale represent better functioning, whereas higher mean scores on the symptom scales represent more symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of age, tumor size, axillary surgery, and adjuvant chemotherapy as sociodemographic and oncological impact factors on the QoL of breast cancer patients is based on clinical studies [1][2][3][4][5][6][7][8][9]. The impact of primary surgical treatment (BCT vs mastectomy), especially in relation to long-term body image, would also have been of interest [3,5], but the very small subgroup of patients treated with mastectomy (8%) did not allow statistical analysis.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…28 The questions about current symptoms were developed by the Munich Cancer Registry (MCR) of the Munich Comprehensive Cancer Center (MCCC) and had already been used in various surveys of breast cancer and rectal cancer patients. [29][30][31] The second part of the questionnaire was the EORTC QLQ-C30, a validated QOL evaluation tool. [32][33][34] This questionnaire contains 30 questions covering five functional scales (physical, emotional, cognitive, social, and role), a global QOL measure, and symptoms including pain, fatigue, diarrhea, and constipation.…”
Section: Procedures and Measuresmentioning
confidence: 99%